2017
DOI: 10.1016/j.apjtm.2017.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, antioxidant and antibacterial activities of essential oil and methanol extract of Artemisia vulgaris and Gaultheria fragrantissima collected from Nepal

Abstract: The HPLC analysis of the methanol extract of A. vulgaris shows the presence of luteolin and morin, whereas G. fragrantissima reveals the presence of rutin and a glycosylated flavonoids. Results reveal that A. vulgaris oil is the rich source of monoterpene and sesquiterpene compounds. Furthermore, A. vulgaris and G. fragrantissima are the rich source of the phenolic and flavonoids compounds and show good antioxidant and antibacterial activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 26 publications
0
49
0
2
Order By: Relevance
“…Subsequently, A. vulgaris leaves extract has shown a reasonable potential of antioxidants activity with the percentage inhibition of 68.06% at 60 μg/ml concentration and ferric reducing power of 0.95 ± 0.05 at100 μg/ ml. The resulted antioxidant properties might be considered due to the high contents of flavonoid compound which act as a scavenging agents for different oxidizing species such as hydroxyl radical and super oxide anion (O2-•) [1]. Iqbal et al reported that the methanol extract of A. annua leaves showed the higher scavenging activities and reducing power comparatively with the other solvents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, A. vulgaris leaves extract has shown a reasonable potential of antioxidants activity with the percentage inhibition of 68.06% at 60 μg/ml concentration and ferric reducing power of 0.95 ± 0.05 at100 μg/ ml. The resulted antioxidant properties might be considered due to the high contents of flavonoid compound which act as a scavenging agents for different oxidizing species such as hydroxyl radical and super oxide anion (O2-•) [1]. Iqbal et al reported that the methanol extract of A. annua leaves showed the higher scavenging activities and reducing power comparatively with the other solvents.…”
Section: Discussionmentioning
confidence: 99%
“…Aromatics and Medicinal plants are one of the main significant sources of phytochemical constituent called secondary metabolites, which have been used widely in most of the pharmaceutical companies [1]. The World Health Organization (WHO) conducted a survey and reported that the total world′s populations of around 80% were depends on traditional knowledge of medicines, especially the medicinal plants for supporting their healthcare [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Among the analysed metabolites, sabinene, β-myrcene, δ-3-carene, γ-terpinene, limonene, α-capaene, octanoic acid, and isocaryophillene were reported to have antimicrobial properties. [14][15][16][17][18][19] Identified metabolites reported to have antimicrobial and antioxidant properties are also tabulated in Table 5. Figure 4A).…”
Section: Gc-ms Analysis Of Eomentioning
confidence: 99%
“…The bestdescribed property of almost every group of flavonoids is their ability to act as antioxidants. The flavonoids seem to be the most powerful compound to protect the body against reactive oxygen species [18].…”
Section: Extract and Fraction Of Daemonorops Dracomentioning
confidence: 99%